Reformasi Pendidikan Islam di Bawah Pengaruh Barat - Apriliani, Wilda; Erman, Erman; Hasnah, Radhiatul (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2024)
The dichotomy between Islamic and Western education creates dualism in the education system. Islamic education, which initially focused on religious teachings, now has to adapt to the modern system adopted from the West. Educational reform has had a positive impact such as the integration of the national education system with Islamic education, increased institutional autonomy, curriculum diversification, and responsiveness to the times. The reform expands access to Islamic education to various levels of society, allowing the younger generation to get quality education. Using the literature study method shows the challenges for Islamic educational institutions in maintaining religious values while meeting the demands of modernity. Reform remains an important step in improving the quality and relevance of Islamic education in Indonesia. The results of the study show that the reform has a positive impact on the integration of the national education system with Islamic education. There is an increase in the autonomy of educational institutions, curriculum diversification, and responsiveness to the challenges of the times. The negative influence of Western domination is still seen through the emergence of dichotomies in education and dependence on Western technology and teaching methods. The reforms have also increased the accessibility of Islamic education to various levels of society, allowing the younger generation to get quality education that is relevant to the times.